Impact of COVID-19 on HIV Testing Among AIDS Institute–Funded Providers in New York State–A Time Series Analysis. (1st January 2023) - O'Grady, Thomas J.; Yuan, Yingchao; Harris, Julie M.; Massaroni, Ronald J.; Fuller, John A.; Tesoriero, James M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: New York State (NYS) was at the intersection of the HIV epidemic and coronavirus disease 2019 (COVID-19) pandemic leading to a disruption in HIV-preventive services. This study sought to determine the impact of the COVID-19 pandemic and mitigation efforts on HIV-testing trends in NYS among AIDS Institute (AI)-funded providers. Methods: We analyzed weekly testing data from the AI Reporting System from January 1, 2017, to June 27, 2021, to fit an interrupted time series model that predicted the expected number of HIV tests among AI-funded providers in NYS had the COVID-19 pandemic not occurred. The actual observed numbers of HIV testing that occurred from weeks beginning March 15, 2020, to June 30, 2021, were compared with the number of HIV tests predicted by the model. Results: In the absence of the COVID-19 pandemic, our model predicted that there would have been 45, 605 HIV tests among AI-funded providers between the weeks beginning March 15, 2020, to June 27, 2021. We observed 20, 742 HIV tests, representing a 54.5% reduction. We observed percent decreases of greater than 50% for HIV testing among AI-funded providers for New York City (52.9%) and rest of state (59.8%) regions, male (50.6%) and female (66.8%) genders, as well as Black (59.2%), Hispanic (52.8%), mixed race (57.5%), other (50.3%), and White (50.1%) race and ethnicities. Conclusion: HIV testing among AI-funded providers in NYS has declined substantially following the COVID-19 pandemic, reflecting decreased access to, and/or demand for, testing among persons at elevated risk for HIV. Initiatives to increase HIV testing and maintain access to HIV prevention services need to be explored following COVID-19.